Reconsidering the Validity of Zero Score’s Grading Practices: Imperatives of Paradigm Shift in Assessment Strategies in Nigerian Universities - IBRAHIM, Abdul-Wahab (Ilorin Journal of Education, 2023)
This paper examined the assessment practices of awarding zero scores as undergraduate students’ grade in a course or test by Lecturers in Nigerian Universities and focused on the validity and usefulness of the practice, as students continue to reap the consequences without benefit. These were with a view to benchmarking stable procedure and ensuring stability and validity in university grades. Hence, the paper explored the concept of zero score measurement, the multidimensional impact of zero score on students’ academic performance and interpretations of zero scores in educational measurement. The assessment and grading issues for undergraduate instruction were examined from the perspective of validity and policy practice. An alternative conceptualization of zero scores as grades, was proposed and explored. Further, the paper concluded that giving zeros as an academic measurement is inequitable and produces failure rather than performance. It was recommended that Lecturers in Nigerian Universities need to adopt technical testing principles to be more relevant to the nature of classroom assessment decision making.